Kekerasan Verbal dalam Media Sosial Facebook - Dwi Yuliantoro Seno Utoro; Susetyo Susetyo; Ria Ariesta (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
Social media in Indonesia has developed rapidly over time. This is supported by increasingly advanced internet infrastructure, such as wifi access, fiber networks, and so on. Indonesians are increasingly active in the world of social media, with a penetration rate of tens of millions of people. The existence of social media certainly has an impact, both positive and negative so that any content can go viral easily. When interacting or communicating using this media, so many people abuse the ethics of socializing in cyberspace by uploading or commenting on posts using harsh words which are called verbal violence. This study aims to determine the form of language used in social media and the form of comments on posts on social media Facebook. This research method uses a qualitative descriptive method. The source of research data comes from social media Facebook, while the data is in the form of verbal abuse comments on Facebook. Data collection techniques using documentation techniques. Data analysis used qualitative analysis techniques and data validity checking techniques performed by checking observation and memberchek persistence. The results showed that the form of the language used in the Facebook sentence had straightforwardness, accuracy, and clarity. Meanwhile, the forms of comments on posts on Facebook in the form of verbal abuse include: swearing, hyperbole, dysphemism, stigmatization, and association with animals. The language of verbal violence on Facebook shows that Indonesian people are still not polite in language, so it becomes input for the government and educational institutions to provide strategic steps to overcome this problem.